Occupation of space and risks of disasters in the Prehispanic time: The ancestral resilience in the low basin of the Chillón River - Ramírez Gamarra, Juana N. (2021)
The Natural Phenomena inherent in the natural processes that occur on the planet, generate chemical physical transformations, which combined with the social aspect of occupation of a particular territorial and environmental scope, cause disasters. These events have been recorded on the north coast of our country, with an age of approximately 10,000 years, so the development of pre-Hispanic societies had to live facing them and adapting to them, leaving in their construction works the capacity of ancestral resilience practiced, which is possible to identify by analyzing and assessing hazards according to Law No. 29664 of the National Disaster Risk Management System.